1992
DOI: 10.1093/forestry/65.4.363-a
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Damage by Mammals in North Temperate Forests: 3. Impact on Trees and Forests

Abstract: The causes of browsing, bark stripping, and fraying damage by deer are examined by reviewing the available literature. Trees species differ in vulnerability and each form of damage occurs within certain age and size classes. Stem morphology has an important influence on bark stripping; lower branches and bark thickening tend to deter stripping in any one species. Site related factors such as hiding cover, snow and soil fertility also influence damage. The data relating deer population density to damage are imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
269
0
7

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 399 publications
(302 citation statements)
references
References 0 publications
5
269
0
7
Order By: Relevance
“…A number of authors mentioned a higher probability of stem infection by S. sanguinolentum (in Picea sitchensis as well as Picea abies) in larger wounds (Löffer 1975;Roll-Hansen, Roll-Hansen 1980;El Atta, Hayes 1987;Gill et al 2000). However, Picea abies is attacked by S. sanguinolentum relatively intensively even in cases of small gaping wounds as supported by this paper and by other papers (Gregory 1986;Gill 1992;Gill et al 2000). Roll-Hansen and Roll-Hansen (1980) or Vasiliauskas et al (1996) reported that wounds larger than 50 cm 2 showed good conditions for infection.…”
Section: Discussionsupporting
confidence: 80%
“…A number of authors mentioned a higher probability of stem infection by S. sanguinolentum (in Picea sitchensis as well as Picea abies) in larger wounds (Löffer 1975;Roll-Hansen, Roll-Hansen 1980;El Atta, Hayes 1987;Gill et al 2000). However, Picea abies is attacked by S. sanguinolentum relatively intensively even in cases of small gaping wounds as supported by this paper and by other papers (Gregory 1986;Gill 1992;Gill et al 2000). Roll-Hansen and Roll-Hansen (1980) or Vasiliauskas et al (1996) reported that wounds larger than 50 cm 2 showed good conditions for infection.…”
Section: Discussionsupporting
confidence: 80%
“…Similarly, no deer browsing of aspen suckers was observed, in line with Rackham (1975) and Joys et al (2004), although both roe and red deer have high preferences for aspen (Gill, 1992a), and aspen is often planted as a fodder crop for wild deer (Worrell, 1995b). Avoidance could be due to elevated levels of secondary compounds in the plant tissues produced as a response to the initial felling, in order to deter further browsing (Karban and Myers, 1989;Gill, 1992b). The American aspen (Populus tremuloides Michx.)…”
Section: Aspen Regrowthmentioning
confidence: 76%
“…Plants may undergo major morphological changes after browsing such as reduced height, and less side shoots combined with reduced foliage density, which can affect growth rate and may result in severe growth loss [11,20]. The physical damage is influenced by the intensity, frequency, and seedling flushing stage at the time of the herbivore attack [19]. Repeated browsing damages the plant more than a single attack, has negative effects on height growth and stem form and can create an imbalance in the shoot-root ratio [12,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The physical damage is influenced by the intensity, frequency, and seedling flushing stage at the time of the herbivore attack [19]. Repeated browsing damages the plant more than a single attack, has negative effects on height growth and stem form and can create an imbalance in the shoot-root ratio [12,19,20]. Severe attacks can even kill seedlings [13,17,19].…”
Section: Introductionmentioning
confidence: 99%